Destination marketing: how to brand territories (Case of Kazakhstan) - Argimbayeva, A. (International School of Economics KAZGUU, Nur-Sultan, 2022)
This work is devoted to studying destination marketing and how to brand territories in the example of Kazakhstan. Over the past 30 years, due to globalisation and geopolitical changes, many countries have thought about the need to develop a country brand. As part of this study, we consider what work has been done to establish the brand of Kazakhstan, in what condition it is now and what are the prospects
Keywords: branding, destination marketing, Nation branding, brand territories